2020
DOI: 10.1007/s42452-020-1967-1
|View full text |Cite
|
Sign up to set email alerts
|

A simple procedure to obtain nanodiamonds from leftover of HFCVD system for biological application

Abstract: Nanodiamonds (NDs) are amongst the most investigated carbon-based nanostructures due to their chemical stability and favorable mechanical properties. Despite the number of works on methods for NDs production, one of the main challenges is to achieve their colloidal stability in aqueous suspension. Additionally, NDs are normally obtained by expensive, complex and time-consuming process. Herein, it was presented a facile method to obtain NDs in aqueous suspension by using columnar structure diamond from Hot-Fila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(74 reference statements)
1
1
0
Order By: Relevance
“…Accordingly, Gismondi et al (2015) [62] also reported cell viability values greater than 80% after incubation of B16-F10 and HeLa cells with detonation ND of 4-5 nm at 200 µg/mL. The low cytotoxicity of ND was also reported in our previous work (Hurtado 2020) [12]. ND of 22-77 nm diameter were obtained from micrometric diamond HFCVD by ultrasonic cavitation.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Accordingly, Gismondi et al (2015) [62] also reported cell viability values greater than 80% after incubation of B16-F10 and HeLa cells with detonation ND of 4-5 nm at 200 µg/mL. The low cytotoxicity of ND was also reported in our previous work (Hurtado 2020) [12]. ND of 22-77 nm diameter were obtained from micrometric diamond HFCVD by ultrasonic cavitation.…”
Section: Discussionsupporting
confidence: 61%
“…The most commonly techniques to produce ND are high pressures and high temperatures (HPHT) [7], plasma-assisted chemical vapor deposition (PACVD), hot filament chemical vapor deposition (HFCVD), explosive detonation [7], laser ablation [3,8,9], and ultrasonic cavitation [10,11]. Recently ND with hydrogenated surface were obtained from leftover of HFCVD system by ultrasonic cavitation [12] and high-energy mill grinding [13]. The ND obtained by explosive detonation have high surface density of oxidized chemical groups that are highly reactive and enable the coupling of different types of molecules [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%